A high-status seventh-century female burial from West Hanney, Oxfordshire - Hamerow, H; Byard, A; Cameron, E; Düring, A; Levick, P; Marquez-Grant, N; Shortland, A (Cambridge University Press, 2015)
In 2009, a metal-detector find of a rare garnet-inlaid composite disc brooch at West Hanney, Oxfordshire, led to the excavation of an apparently isolated female burial sited in a prominent position overlooking the Ock valley. The burial dates to the middle decades of the seventh century, a period of rapid socio-political development in the region, which formed the early heartland of the Anglo-Saxon kingdom of Wessex. The de luxe brooch links the wearer to two other burials furnished with very similar brooches at Milton, some 10km to the east and only c 1km from the Anglo-Saxon great hall complex at Sutton Courtenay / Drayton, just south of Abingdon. All three women must have been members of the region’s politically dominant group, known as the Gewisse. The burial’s grave goods and setting add a new dimension to our understanding of the richly furnished female burials that are such a prominent feature of the funerary record of seventh-century England.